The effect of standalone audio-visual feedback devices on the quality of chest compressions during laypersons' CPR training: A Systematic review and meta-analysis - Kahsay Desale Tewelde; Peltonen Laura-Maria; Rosio Riitta; Tommila Miretta; Salanterä Sanna (United Kingdom, 2025)
Aim: Individual studies that investigated the effect of standalone audio-visual feedback (AVF) devices during laypersons' cardiopulmonary resuscitation (CPR) training have yielded conflicting results. This review aimed to evaluate the effect of standalone AVF devices on the quality of chest compressions during laypersons' CPR training.
Method and result: Randomized controlled trials of simulation studies recruiting participants without actual patient CPR experience were included. The intervention evaluated was the quality of chest compressions with standalone AVF devices vs without AVF devices. Databases, such as PubMed, Cochrane Central, Embase, CINAHL, Web of Science, and PsycINFO, were searched from January 2010 to January 2022. The risk of bias was assessed using the Cochrane risk of bias tool. A meta-analysis alongside a narrative synthesis was used for examining the effect of standalone AVF devices.Sixteen studies were selected for this systematic review. A meta-analysis revealed an increased compression depth of 2.22 mm [95% CI, 0.88-3.55), p = 0.001] when participants performed CPR using the feedback devices. Besides, AVF devices enabled laypersons to deliver compression rates closer to the recommended range of 100-120 per min. No improvement was noted in chest recoil and hand positioning when participants used standalone AVF devices.
Conclusion: The quality of the included studies was variable, and different standalone AVF devices were used. Standalone AVF devices were instrumental in guiding laypersons to deliver deeper compressions without compromising the quality of compression rates. However, the devices did not improve the quality of chest recoil and placement of the hands.